Evaluation of the phenyl-bonded silica-based sorbent for pre-concentration of the booster antifouling biocides zinc pyrithione, zineb and ziram using solid-phase extraction technique and inductively coupled plasma mass spectrometry - Rolisola, Ana Marta Cavinato Marchini [UNESP]; Menegário, Amauri Antônio [UNESP]; Yabuki, Lauren Nozomi Marques [UNESP]; Polese, Luciana [UNESP]; Kiang, Chang Hung [UNESP] (Ecletica Quimica, 2020)
A robust method of solid-phase extraction technique with use of the phenyl-bonded silica-based sorbent (Si-PH sorbent) for pre-concentration of three booster antifouling biocides: Zinc pyrithione, Zineb and Ziram in ultrapure water fortified and estuarine water sample was evaluated for zinc determination by collision cell technology-inductively coupled plasma-mass spectrometry (CCT-ICP-MS). Decontamination process to remove metals and prevent (trans-) metallization of the Si-PH sorbent with 20 mL of nitric acid 0.006 mol L-1 was performed. This proposed solid-phase extraction efficiency of three booster antifouling biocides by the phenyl-bonded silica-based sorbent (Si-PH sorbent) was evaluated in 40 mL of ultrapure water fortified sample (40 μg L-1 of the zinc biocides). The adsorption of zinc pyrithione, Zineb and Ziram were 94.2 ± 0.1%, 85.13 ± 0.04% and 93.35 ± 0.09%, respectively. The limit of detection and limit of quantification values obtained were 0.66 μg L-1 and 2.19 μg L-1, respectively. Good recoveries of zinc pyrithione (85 ± 2%), Zineb (89 ± 5%) and Ziram (111 ± 2%) in the elution step for booster antifouling biocides from the fortified estuarine water were obtained.